PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (SAP), KOMPETENSI SUMBER DAYA MANUSIA (SDM) DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN SKPD (StudipadaPemerintah Daerah Kota Dumai) - Triwahyuni, Mustika; Azlina, Nur; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the influence of appliance government accounting standars (sap), competence of human resource (sdm), and appliance of financial accounting system toward the quality of government financial statement. The research was conducted on the regional work units of Dumai. This study used purposive sampling method. The sample in this study is the Secretary of SKPD, treasurer of SKPD, Head of Sub Division of Finance, and Chief Financial administrator. The sample used in this study were 66 respondents. The statistical method used to test the hypothesis of the research is multiple linear regression analysis using SPSS. The results showed that the variables of appliance government accounting standards and appliance of financial accounting system toward have effect on the quality of financial statement. While the competence of human resource do not have effect on the quality of financial statement. The independent variable can explain the dependent variable of 76,8%. While the remaining 23,2% is explained by other independent variable that are not observed in this study.Keywords: Government Accounting, Competence, Financial Accounting, and Quality of Financial